Problems of providing high-quality raw materials of the bakery enterprises - Dunda, Svetlana (My University, 2013)
Problems of providing high-quality raw materials of the bakery enterprises are considered. Розглянуто проблеми забезпечення якісною сировиною хлібопекарних підприємств.
Keywords: quality; bakery enterprises; flour; якість; хлібопекарні підприємства; борошно; кафедра економіки праці та менеджменту